130k views
4 votes
(1+iroot12)-(-8+iroot3)

1 Answer

1 vote

For this case we must simplify the following expression:


(1 + i \sqrt {12}) - (- 8 + i \sqrt {3})

We apply distributive property to the terms of the second parenthesis considering that:


- * - = +\\- * + = -

So:


1 + i \sqrt {12} + 8-i \sqrt {3} =

Rewriting:


1 + i \sqrt {2 ^ 2 * 3} + 8-i \sqrt {3} =\\1 + 2i \sqrt {3} + 8-i \sqrt {3} =

Adding similar terms:


1 + 8 + 2i \sqrt {3} -i \sqrt {3} =\\9 + i \sqrt {3}

Answer:


9 + i \sqrt {3}

User Coreen
by
4.4k points